The bishops of the Church of England in Canada and Newfoundland [electronic resource] : being an illustrated historical sketch of the Church of England in Canada, as traced through her episcopate - Mockridge, Charles H. (Charles Henry), 1844-1913. (London : Church Bells; Toronto : F.N.W. Brown, 1896)
Electronic reproduction. Mode of access: Internet. 44